2014
DOI: 10.1111/jsap.12225
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of urine and bladder or urethral mucosal biopsy culture obtained by transurethral cystoscopy in dogs with chronic lower urinary tract disease: 41 cases (2002 to 2011)

Abstract: There was a good agreement between pathogen identification from urine and lower urinary tract mucosal cultures. These results do not support the utilisation of transurethral cystoscopy to obtain biopsy samples for culture in dogs with urinary tract infection and positive urine culture. Individual cases with possible chronic urinary tract infection and negative urine culture may benefit from transurethral cystoscopy to obtain biopsies for culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
7
2
1
Order By: Relevance
“…Sensitivity testing revealed that 7 out of the 12 positive urine cultures were resistant to at least 1 commonly administered oral antibiotic. In 2 dogs, urine culture was negative; however, bladder mucosal biopsy was positive which is in disagreement with previous reports . This discrepancy might be explained by the invasion of superficial bladder epithelial cells and submucosa by bacteria, even if the isolated bacteria in our cases were not E. coli , which has been previously described in host cells with type‐1 fimbriae‐mediated invasion.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Sensitivity testing revealed that 7 out of the 12 positive urine cultures were resistant to at least 1 commonly administered oral antibiotic. In 2 dogs, urine culture was negative; however, bladder mucosal biopsy was positive which is in disagreement with previous reports . This discrepancy might be explained by the invasion of superficial bladder epithelial cells and submucosa by bacteria, even if the isolated bacteria in our cases were not E. coli , which has been previously described in host cells with type‐1 fimbriae‐mediated invasion.…”
Section: Discussioncontrasting
confidence: 83%
“…In 2 dogs, urine culture was negative; however, bladder mucosal biopsy was positive which is in disagreement with previous reports. 13,32,33 This discrepancy might be explained by the invasion of superficial bladder epithelial cells and submucosa by bacteria, 34 even if the isolated bacteria in our cases were not E. coli, which has been previously described in host cells with type-1 fimbriae-mediated invasion. Even if this was present in a small number of dogs, we recommend urine culture and bladder mucosal biopsy culture in dogs undergoing cystoscopy for RUTI.…”
Section: Histopathologymentioning
confidence: 48%
See 1 more Smart Citation
“…Hierbei scheint es keine Rolle zu spielen, ob bei Narkoseeinleitung oder erst nach Probenentnahme bei Zystotomien prophylaktisch antimikrobiell wirksame Substanzen verabreicht werden [8]. Im Falle eines Erregernachweises im Urin ist eine mikrobiologische Untersuchung von Bioptaten oder Zystolithen scheinbar nicht notwendig, da hier hinsichtlich der Befunde eine sehr gute Übereinstimmung besteht [49].…”
Section: Lokalisation Der Harnsteineunclassified
“…Escherichia coli is the most common bacterial pathogen associated with UTIs in dogs, followed by Staphylococcus , Proteus , Klebsiella , and Pseudomonas species . Previous in vitro studies have demonstrated that almost all clinical E. coli and Staphylococcus pseudintermedius isolates from dogs can produce biofilms .…”
mentioning
confidence: 99%